Effects of Chemotherapy-Induced Neutropenia on Overall Survival in Patients With Unresectable or Metastatic Urothelial Carcinoma to Gemcitabine Plus Cisplatin Combination Chemotherapy. Issue 7 (July 2019) - Yamamoto, Keisuke; Sasano, Tomomi; Tsuji, Daiki; Ishizuka, Yuichi; Tokou, Umi; Nakamichi, Hidenori; Yoneda, Tatsuaki; Shiokawa, Mitsuru; Yabe, Katsushige
Background: Chemotherapy-induced neutropenia (CIN) is an important dose-limiting toxicity of chemotherapy. However, evidence suggests that the occurrence of CIN may be predictive of treatment outcome. Indeed, studies have revealed that the onset of CIN is associated with a good chemotherapeutic response.Objective: The purpose of this study was to investigate the association between the onset of CIN and overall survival in patients with unresectable or metastatic urothelial carcinoma (UC) who received a combination regimen of gemcitabine and cisplatin (GC).Methods: Medical records from 56 patients with unresectable or metastatic UC who were treated with a combination GC regimen between December 2005 and May 2016 were retrospectively analyzed to investigate the association between CIN development and survival.Results: The median duration of survival was 521 days (95% CI = 147-193 days) for patients with severe CIN and 287 days for patients without CIN. Additional multivariate analysis revealed that both the presence of severe CIN (hazard ratio [HR] = 0.399; 95% CI = 0.180-0.880, P = 0.023) and baseline hemoglobin (HR = 2.167; 95% CI = 1.170-4.014, P = 0.014) represented independent prognostic factors for the survival of patients with unresectable or metastatic UC receiving GC treatment.Conclusion and Relevance: CIN onset was associated with longer survival in patients receiving GC therapy for unresectable or metastatic UC, suggesting that neutropenia monitoring during GC chemotherapy may be predictive of treatment efficacy.